2019
DOI: 10.1016/j.omtn.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the IL-6-Signaling Pathway in Liver Cells by miRNAs Targeting gp130, JAK1, and/or STAT3

Abstract: Interleukin-6 (IL-6)-type cytokines share the common receptor glycoprotein 130 (gp130), which activates a signaling cascade involving Janus kinases (JAKs) and signal transducer and activator of transcription (STAT) transcription factors. IL-6 and/or its signaling pathway is often deregulated in diseases, such as chronic liver diseases and cancer. Thus, the identification of compounds inhibiting this pathway is of interest for future targeted therapies. We established novel cellular screening systems based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 101 publications
1
25
0
Order By: Relevance
“…Given the importance of IL-6 signalling in the host immune response to S.epidermidis infection, we investigated the mechanism(s) of IL-6 regulation. The IL-6 signalling pathway is regulated by multiple miRNAs (Servais et al, 2019). miR-142 is one of the major miRNAs that has been shown to have important functions in infections and inflammation (Shrestha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of IL-6 signalling in the host immune response to S.epidermidis infection, we investigated the mechanism(s) of IL-6 regulation. The IL-6 signalling pathway is regulated by multiple miRNAs (Servais et al, 2019). miR-142 is one of the major miRNAs that has been shown to have important functions in infections and inflammation (Shrestha et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…miRNA-mediated modulation is one of the important mechanisms of regulation of different genes of this pathway (Tanaka et al, 2016). miR-142 is one of the several miRNAs that has been shown to be involved in the IL-6 signalling pathway (Servais et al, 2019). miR-142-3p has been reported to target il-6 in models of endotoxin-challenge and age-related studies (Liu et al, 2016; Sun et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Our findings indicated that the biological behaviour of osteoclasts is modulated by WKYMVm. [36][37][38] Moreover, CD9 stabilizes gp130 to activate STAT3 in glioma stem cells by preventing its ubiquitin-dependent lysosomal degradation. The NF-κB signalling pathway is considered essential for osteoclast differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The JAK/STAT3 pathway transmits extracellular information to the nucleus to modulate cell proliferation, apoptosis, differentiation and angiogenesis [19][20].…”
Section: Discussionmentioning
confidence: 99%